PIYAGĔM SUKAPURA (1641 M): GEOPOLITIK KERAJAAN MATARAM ISLAM DI PRIANGAN - Muhamad Alnoza (AMERTA, 2022)
Abstract, Piyagem Sukapura (1641 Ad): Geopolitics of Islamic Mataram Kingdom in Priangan, Piyagem is epigraphic evidence of the hegemony establishment of the Islamic Mataram Kingdom in the Priangan area. The period of the Islamic Mataram Kingdom’s power began with the suwer of the King of Sumedang, Raden Suriadiwangsa, to Sultan Agung in 1620. One of the piyagem issued by Sultan Agung while reigning in Priangan was Piyagem Sukapura. This metal inscription with the New Javanese script outlines the information on the three regencies’ establishment in Priangan in 1641 AD. This research further seeks to answer the problem regarding the relationship between the establishment of the three regencies in Priangan and geopolitical phenomena in the Islamic Mataram Kingdom. The research steps taken included data collection and analysis, in which the primary data source of this study was the transliteration of Piyagem Sukapura, while the secondary sources used as comparisons included the Sajarah Sukapura and Sajarah Cikundul manuscripts. In the end, this research concludes that Piyagem Sukapura is closely related to Sultan Agung’s geopolitical strategy after the rebellion of Dipati Ukur and the failure of the conquest of Batavia. Keyword: Geopolitic, Piyagem Sukapura; Priangan; Sultan Agung   Abstrak, Piyagem merupakan bukti epigrafis dari berdirinya hegemoni kuasa Kerajaan Mataram Islam di daerah Priangan, Rentang waktu kekuasaan Kerajaan Mataram Islam dimulai sejak menyerahnya Raja Sumedang, Raden Suriadiwangsa, kepada Sultan Agung di tahun 1620. Salah satu piyagem yang dikeluarkan Sultan Agung selama memerintah di Priangan adalah Piyagem Sukapura. Prasasti logam beraksara dan berbahasa Jawa Baru ini, menguraikan keterangan pendirian tiga kabupaten di Priangan pada tahun 1641 M. Penelitian ini lebih lanjut berusaha untuk menjawab permasalahan soal kaitan antara pendirian tiga kabupaten di Priangan tersebut dan fenomena geopolitik di Kerajaan Mataram Islam. Adapun langkah-langkah penelitian yang diambil meliputi pengumpulan data dan analisis. Sumber data primer penelitian ini adalah transliterasi Piyagem Sukapura, sedangkan sumber sekunder yang dijadikan pembanding di antaranya manuskrip Sajarah Sukapura dan Sajarah Cikundul. Penelitian ini di akhir menghasilkan simpulan bahwa Piyagem Sukapura berkaitan erat dengan strategi geopolitik Sultan Agung pasca pemberontakan Dipati Ukur dan kegagalan penaklukan Batavia. Kata Kunci: Geopolitik; Piyagem Sukapura; Priangan; Sultan Agung.